The contribution of demyelination to axonal loss in multiple sclerosis. - DeLuca, G; Williams, K; Evangelou, N; Ebers, G; Esiri, M (2006)
The traditional notion that multiple sclerosis is a primary demyelinating disease has led to a plaque-centred view of both aetiology and the pathogenesis of disease progression. The presence of axonal loss has received increasing recognition. However, the relative roles of demyelination and axonal loss have not been fully clarified in multiple sclerosis nor have their possible interrelationships been elucidated. Post-mortem material from the cerebrum, brainstem and spinal cord of 55 multiple sclerosis patients (29 males) with an age range of 25-83 years (mean = 57.5 years) and length of disease history ranging from 2 to 43 years (mean = 17.1 years) was stained for myelin. Plaque load was calculated by summing the relative proportion of plaque area compared with total white matter area of the corticospinal and sensory tracts at each level. This was related to estimates of axonal density and of total axon number in these tracts in the spinal cord. Our results indicate that plaque load did not correlate with brain weight. Unexpectedly, after adjusting for sex, age and duration of disease, correlations between total plaque load and axonal loss in both the corticospinal tract and sensory tracts were weak or absent at each level investigated. Since there was little correlation between plaque load and axonal loss, the possibility that demyelination is not the primary determinant of spinal cord axonal loss warrants consideration.